2022
DOI: 10.1093/hsw/hlac033
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Depression in Ohio Social Workers during the COVID-19 Pandemic: The Buffering Role of Social Connectedness

Abstract: Although social workers have an elevated risk of infection with COVID-19, no previous studies have investigated the virus’s impact on practitioners. Using survey data (N = 441), this study identified associations between stress, depression, and COVID-related factors and explored the role of social connectedness as a moderator for mental health among Ohio social workers. The results of the study showed that among social workers with a positive COVID-19 diagnosis, 70 percent experienced moderate/high levels of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Rather, social connectedness plays a direct positive role in influencing the main source of stress [ 84 ]. For the mediation model of positive perfectionism, social connectedness moderated the association between positive perfectionism and perceived stress, in other words, the interaction between social connectedness and positive perfectionism alleviated nurses’ perceived stress levels, which is consistent with the findings of Park et al [ 51 ]. Therefore, dissecting the pathways in which social connectedness influences the alleviation of individual perceived stress based on the personality trait of perfectionism is an important way for nursing managers to provide effective psychological interventions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Rather, social connectedness plays a direct positive role in influencing the main source of stress [ 84 ]. For the mediation model of positive perfectionism, social connectedness moderated the association between positive perfectionism and perceived stress, in other words, the interaction between social connectedness and positive perfectionism alleviated nurses’ perceived stress levels, which is consistent with the findings of Park et al [ 51 ]. Therefore, dissecting the pathways in which social connectedness influences the alleviation of individual perceived stress based on the personality trait of perfectionism is an important way for nursing managers to provide effective psychological interventions.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, social connectedness, defined as an individual’s self-perception of closeness to others in their surroundings [ 49 ], plays an active role in reducing perceived stress [ 50 , 51 ]. Based on Maslow’s Hierarchy of Needs theory, the need for love and belonging is a fundamental human need, which leads individuals to actively seek out social connection that can satisfy this need, such as families and public welfare organizations, in order to alleviate negative emotions and positively regulate their state under high stress [ 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social connectedness plays a positive role in directly in uencing the main source of stress generation, while indirectly mitigating stress levels [84] . For the mediated model of positive perfectionism, social bonding moderates the association between positive perfectionism and perceived stress, in other words, the interaction between social connectedness and positive perfectionism alleviated nurses' perceived stress levels, which is the same as the ndings of Park et al [54] . Therefore, dissecting the pathways of in uence of social connectedness in alleviating individual perceived stress based on the personality trait of bidirectional perfectionism is an important way for nursing managers to conduct effective psychological interventions.…”
Section: Discussionsupporting
confidence: 68%
“…Additionally, social connectedness, de ned as an individual's self-perception of closeness to others in their surroundings [52] , plays an active role in reducing perceived stress [53,54] . Clinical nurses, in addition to the social signi cance of the daily nursing behaviors themselves, participate as individuals in group work and, more importantly, seek to gain a sense of self-worth and connection with others.…”
mentioning
confidence: 99%
“…For example, a study among 842 union grocery store workers in California in late 2020 showed that COVID-19-related fear, workplace threat perception, and overall perceived stress affected workers' mental health [18]. Increased symptoms of depression and anxiety or higher psychological distress were also observed among social workers, teachers or bank employees during the COVID-19 pandemic [19][20][21]. In addition, the baseline survey underlying this study during the second and third pandemic waves in Germany (December 2020 to June 2021) with a retrospective survey on mental distress in spring 2020, showed that non-healthcare professionals with high and probable occupational SARS-CoV-2 infection risk (OSIR) were at higher risk for depressive and anxiety symptoms [22].…”
Section: Introductionmentioning
confidence: 99%